Serum Mannose-binding Lectin in Patients on Peritoneal Dialysis Compared With Healthy Individuals (Iranian Journal of Kidney Diseases, 2016)
Introduction. The increased susceptibility to infection in patients with end-stage renal disease is probably secondary to the impaired immune defense in uremia. Mannose-binding lectin (MBL) has an important role in host defense through activation of the lectin complement pathway. The aim of this study was to measure serum MBL level in peritoneal dialysis patients and compare it with a healthy group. Materials and Methods. Seventy peritoneal dialysis patients and 70 healthy individuals were enrolled in this study. Serum MBL levels were measured by an enzyme-linked immunosorbent assay kit using the mannan molecule. In addition, serum C-reactive protein and albumin levels were measured to determine whether there is a correlation between serum MBL level and these two parameters. Results. The mean serum MBL level was 2.32 ± 2.54 µg/mL (range, zero to 6.93 µg/mL) in the patients group and 1.80 ± 2.14 µg/mL (range, zero to 6.97µg/mL) in the control group (P = .19). No significant correlation was detected between age and serum MBL level in either the groups. In the patients group, no significant correlation was found between serum MBL and C-reactive protein levels or MBL and albumin levels. There were no correlation between duration of peritoneal dialysis and MBL or dialysis adequacy and MBL, either. Conclusions. This study did not find MBL deficiency in peritoneal dialysis patients as compared to the healthy individuals.